2020
DOI: 10.1161/circheartfailure.120.007094
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure and Shared Decision-Making: Patients Open to Medication-Related Cost Discussions

Abstract: Background: Discussions of medication costs between patients and clinicians are infrequent and often suboptimal. In the context of recently introduced drugs that are effective but expensive, patients with heart failure with reduced ejection fraction provide an ideal population to understand the perspectives of patients with chronic illness on medication cost and cost discussions. Methods: To explore patients’ perspectives on discussing out-of-pocket med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Prior research has shown that patients may not disclose barriers due to embarrassment or doubt that providers can help. 80 , 81 Patients may not discuss cost unless asked, 82 such as when providers note adherence problems. 23 , 60 Similarly, we found that information about challenges might be elicited only after prescriptions went unfilled.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that patients may not disclose barriers due to embarrassment or doubt that providers can help. 80 , 81 Patients may not discuss cost unless asked, 82 such as when providers note adherence problems. 23 , 60 Similarly, we found that information about challenges might be elicited only after prescriptions went unfilled.…”
Section: Discussionmentioning
confidence: 99%
“…Although integrating price into clinical decisions rarely occurs today, price is an important consideration for initiating medication discussions that should be on the table during clinical encounters, and available evidence suggests that patients agree. 8 , 26 …”
Section: Discussionmentioning
confidence: 99%
“… 34 Integrating medication cost discussions into shared decision‐making may present an opportunity to mitigate financial toxicity and help patients make decisions that cohere with their preferences and personal financial constraints and goals. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Such costsharing mechanisms exist to address moral hazard and prevent overconsumption of medical resources, but their complexity often confuses patients, 13 who turn to their clinicians for assistance. [14][15][16][17][18][19][20] Although patients may not expect clinicians to have all the answers, they do report hoping for changes in prescription patterns or referrals to pharmaceutical assistance programs when out-of-pocket costs are projected to be high. 21,22 Physician experts and patient advocacy groups have recommended that communication about the financial trade-offs of potential treatment options become part of routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Such cost-sharing mechanisms exist to address moral hazard and prevent overconsumption of medical resources, but their complexity often confuses patients, 13 who turn to their clinicians for assistance. 14 , 15 , 16 , 17 , 18 , 19 , 20 Although patients may not expect clinicians to have all the answers, they do report hoping for changes in prescription patterns or referrals to pharmaceutical assistance programs when out-of-pocket costs are projected to be high. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%